Comprehensive analysis of offshore wind-photovoltaic hybrid systems: unveiling state-of-the-art autonomous components for maritime applications - Popa, Ciprian; Popa, N-S; Isac, H; Deliu, A-D; Andronic, C (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This paper conducts a comprehensive analysis of offshore wind-photovoltaic hybrid systems, presenting autonomous components tailored for maritime applications. Focusing on the critical role of these systems in supplying electricity to regions with limited infrastructure, particularly maritime zones, the study explores economic advantages over traditional power line installations, emphasizing remote areas. Key components, including battery storage, autonomy, battery selection (with a spotlight on lead-acid batteries), charge controllers, inverters, and the integration of Automatic Identification System (A.I.S.) for maritime safety, are discussed. The article concludes by underscoring the significance of power supply buoys for ship safety and efficient refueling near hybrid systems.